Dietary Patterns among Eight Grade Adolescents and their Impact on Dietary Adequacy - Zeida Bárbara Alejo; Amarelis Rodríguez Fuente; Daysi López Sosa; Pilar Almaguer Sabina (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Background: the study of dietary patterns in adolescence becomes of great importance because at this stage individuals acquired eating habits that they will keep throughout their lives. These habits, if not adequate, may increase the risk of chronic diseases in adult ages. Objective: To determine nutritional patterns of eighth grade students and their impact on dietary adequacy. Methods: descriptive study including a universe integrated by all eight grade students in the 5 de Septiembre Junior High School of Cienfuegos. Through simple random sampling, 59 teenagers were selected to be administered two surveys: one on food preferences and another one on a recall of their meals in the last 24 hours. The surveys were prepared by the Institute of Nutrition and Food Hygiene. Results: students preferred fried and sugary foods; only 3.38% received the recommended iron intake; 49, 15% of children received more than 60% of energy from carbohydrates and 59.32% received low amounts of proteins. Conclusions: There are still gaps in these students' nutritional behavior. The major concerning points are the low energy intake and the fact that it is mainly based on carbohydrates, while the deficit in proteins intake, iron and fat has reached a critical point in more than half of our patients.